Practical theology: charismatic and empirical perspectives - Cartledge, Mark J. (Studies in pentecostal and charismatic issues, 2003)
Mark Cartledges`s new book is unique integrating charismatic and empirical perspectives in practical theology. It exemplifies both qualitative and quantitative methods of research, and suggests a way forward for the emerging field of charismatic theology.